Mechanisms of Autoimmune Cell in DA Neuron Apoptosis of Parkinson's Disease: Recent Advancement. (14th December 2022) - Zheng, Zijian; Zhang, Shushan; Zhang, Hanwen; Gao, Zhongzheng; Wang, Xiangrong; Liu, Xinjie; Xue, Cheng; Yao, Longping; Lu, Guohui
Abstract : Parkinson's disease (PD) is a prevalent neurodegenerative disorder that manifests as motor and nonmotor symptoms due to the selective loss of midbrain DArgic (DA) neurons. More and more studies have shown that pathological reactions initiated by autoimmune cells play an essential role in the progression of PD. Autoimmune cells exist in the brain parenchyma, cerebrospinal fluid, and meninges; they are considered inducers of neuroinflammation and regulate the immune in the human brain in PD. For example, T cells can recognize α -synuclein presented by antigen-presenting cells to promote neuroinflammation. In addition, B cells will accelerate the apoptosis of DA neurons in the case of PD-related gene mutations. Activation of microglia and damage of DA neurons even form the self-degeneration cycle to deteriorate PD. Numerous autoimmune cells have been considered regulators of apoptosis, α -synuclein misfolding and aggregation, mitochondrial dysfunction, autophagy, and neuroinflammation of DA neurons in PD. The evidence is mounting that autoimmune cells promote DA neuron apoptosis. In this review, we discuss the current knowledge regarding the regulation and function of B cell, T cell, and microglia as well as NK cell in PD pathogenesis, focusing on DA neuron apoptosis to understand the disease better and propose potential target identification for the treatment in the early stages of PD. However, there are still some limitations in our work, for example, the specific mechanism of PD progression caused by autoimmune cells in mitochondrial dysfunction, ferroptosis, and autophagy has not been clarified in detail, which needs to be summarized in further work.